Fracture resistance of overtly flaring root canals filled with resin-based obturation material - Salma B Abdo; Aziza H Eldarrat (Dental Research Journal, 2013)
Background: Reinforcement of root canals obturated with Resilon was reported by several investigators, but no studies reported the reinforcement of overtly flared root canals obturated with Resilon material. The aim of this study was to investigate the fracture resistance of overtly flared root canals filled with Resilon as compared to similar root canals filled with gutta-percha (GP). Materials and Methods: Sixty single-rooted premolars were divided randomly into six groups. Group 1 served as control group. The control group was sub-divided into two groups, a negative group and a positive group. The negative group consisted of root canals that were only cleaned from residual pulpal tissues, however, the positive group had prepared and overtly flared root canals without obturation. Groups 2 and 4 were shaped using 0.04 taper rotary files, while groups 3 and 5 were shaped using 0.06 taper rotary files. Before obturation, the last four groups were further flared coronally with a reverse cone diamond bur. Groups 2 and 3 were obturated with GP and a resin-based sealer, while groups 4 and 5 were obturated with Resilon and Epiphany self-etching primer and Epiphany sealer. Roots were then fixed into a universal testing machine and vertically loaded until fracture. SPSS software (Release 9.0 for Windows, SPSS, Chicago, USA) was used to perform the statistical analysis. Results: Fracture resistance measurements showed that there were differences in resistance to fracture among the experimental groups (ANOVA, P < 0.0001). Mean values of the loading force applied to the negative control group were the highest at 1.81 KN, whereas the mean values for the Resilon groups (Groups 4 and 5) at 1.13 KN and 1.54 KN were found to be higher than the GP groups (Groups 2 and 3) at 0.45 KN and 0.88 KN, respectively. Tukey′s post hoc test showed that there was no statistical difference between the mean values of the negative control group and Group 5 (P = 0.69). Conclusion: Obturation of overtly flared roots with Resilon material increased the resistance of these teeth to vertical root fracture.